Research on Network Optimization Strategy of Ultra-Broadband CMNet Metro Network - Quanze Jiang; Zhiyuan Lai; Fangrong Chen (Dianxin kexue)
From the competitive situation of internet broadband services in domestic operators，CMNet MAN business network architecture situation and existing problems were analyzed combined with the trends of the broadband business application development.The plaftorm construction of optimizing resource control mobile CMNet MAN was raised under conditions of ultra-broadband，and the sink service control layer BRAS and aggregation switches，optimized WLAN bearer，the CMNet metro and transport network joint networking strategy were also proposed.